2022
DOI: 10.1007/s11657-022-01109-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vitamin D deficiency, body composition, and physical/cognitive functions

Abstract: Summary Vitamin D deficiency is still an important subject due to its significant effects on various tissues and functions. We found a relationship between vitamin D deficiency and increase in adipose tissue thicknesses. This situation reveals the importance of vitamin D supplementation, the harms of weight gain and obesity, and the importance of a balanced diet. Purpose Although the relationship between vitamin D (VitD) levels with body composition and physical/cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this regard, Wen et al (2018) showed vitamin D deficiency in pregnant mice results in the proliferation and differentiation of pre‐adipocytes, alterations of gene methylation, and obesity in offspring. Furthermore, Doğan et al (2022) demonstrated that vitamin D deficiency is related to BMI, and independently increased body visceral fat (Doğan et al, 2022). Although we did not evaluate the visceral fat of the whole body in this study, the results show that the visceral fat of the right and left epididymis increased non‐significantly in the vitamin D deficiency group compared with the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Wen et al (2018) showed vitamin D deficiency in pregnant mice results in the proliferation and differentiation of pre‐adipocytes, alterations of gene methylation, and obesity in offspring. Furthermore, Doğan et al (2022) demonstrated that vitamin D deficiency is related to BMI, and independently increased body visceral fat (Doğan et al, 2022). Although we did not evaluate the visceral fat of the whole body in this study, the results show that the visceral fat of the right and left epididymis increased non‐significantly in the vitamin D deficiency group compared with the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the inhibitor significantly reduced obesity in MRL/LPR mice. Other studies 17,18 have revealed a correlation between VitD deficiency and tissue fat thickness. That supplementation with VitD3 can reduce weight gain and fat accumulation in mice has confirmed, and the study showed that the body weight of C57BL/6 mice on a high‐fat diet changed significantly after continuous supplementation with VitD3 for 10 weeks 19,20 .…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the tendency of shift workers to eat meals at irregular times and their tendency to eat a diet rich in fatty and junk food could lead to a reduced dietary intake of vitamin D [ 13 , 14 ]. It is also known that shift workers tend to have a BMI higher than the general population [ 15 , 36 , 37 ], a factor that could lead to the increased sequestration of vitamin D in adipose tissue and, consequently, lower values of circulating vitamin D [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%